Experiences and Perspectives of Women Veterans Use of the Veterans’ Health Administration Services - (:unkn) unknown (My University, 2022)
Women make up 10% of the veteran population. With a projected increase of up to 16% by 2043, this is the fastest-growing demographic in the US military (National Center for Veterans Analysis and Statistics, 2017). This population may have experiences unique from their non-military counterparts such as military sexual trauma (MST), environmental exposures, post-traumatic stress disorder (PTSD), and stress related to their military occupation that may predispose this group to decreased quality of life (QOL). In recent years, the Veterans Health Administration (VA) healthcare system has attempted to increase the healthcare accessibility and services provided to the growing number of women veterans (WVs) who get care from the VA. Because only 37% of WVs are established VA patients, it can be assumed that WVs are receiving their care outside of the VA or not obtaining healthcare services at all. Additionally, 30% of WVs who seek healthcare at the VA left within the first three years of use. A qualitative study using thematic analysis was conducted to identify the experiences and perspectives of WVs who use the Veterans Affairs Healthcare System and to understand the barriers and frustrations WVs face when using the VA. Four major themes were identified: quality of care received at the VA, barriers to receiving care at the VA, frustrations with the system, and private insurance supplementation. The study found many WVs experience barriers and frustrations when using the system, and some prefer civilian care over the VA to avoid these challenges. However, if the care were more gender-focused, participants expressed that they would prefer the VA as it is important to be connected to others who understand military service.
Keywords: female veteran; VA; VA healthcare system; veterans affairs administration; women veteran health; women veterans